A novel variant of the GPR143 gene causes congenital nystagmus and ocular albinism in a Vietnamese family - Nguyen, Khanh Linh; Nguyen Huu , Hong Thu; Hoang, Cuong; Nguyen, Ha Hai; Pham Thi, Pham Thi Minh Chau (Academia Journal of Biology, 2026)
Ocular albinism is an X-linked recessive inherited syndrome resulting from the variants in the G protein-coupled receptor 143 (GPR143) gene. This condition affects patients' vision, characterized by nystagmus, reduced visual acuity, photophobia, retinal hypopigmentation, and foveal hypoplasia, while having minimal effect on skin or hair pigmentation. This study aims to investigate the genetic factor relating to ocular hypopigmentation and nystagmus symptoms in a large family with multiple generations of affected males, which is predicted to be associated with the X-linked inherited model. The first member of this family involved in the genetic examination was a woman with a normal eye phenotype. She had an unaffected daughter and a son diagnosed with congenital nystagmus and retinal hypopigmentation. Her husband did not have any family history of nystagmus or other ocular abnormalities. Whole-exome sequencing revealed that she harbored a heterozygous variant, c.501_503delGCT (p.Leu168del), in the GPR143 gene on the X chromosome, which is known to be related to nystagmus and ocular albinism. The Sanger sequencing showed that this variant presented as heterozygous and hemizygous states in her daughter and her son, respectively. This variant is novel because it is absent in our in-house WES database of 600 Vietnamese and other databases. Our study has extended the understanding of molecular genetics associated with X-linked ocular albinism syndrome in Vietnam, contributing to the rapid, effective diagnosis of patients in Vietnam.